Composition of Suberin Extracted upon Gradual Alkaline Methanolysis of Quercus suber L. Cork (Journal of Agricultural and Food Chemistry, 2000)
The monomeric composition of suberin extracts obtained by gradual alkaline methanolysis of Quercus suber cork was determined by gas chromatography?mass spectrometry (GC-MS). Results show that 1-alkanols and alkanoic and α,?-alkanedioic acids are preferentially removed upon mild alkaline conditions, whereas mid-chain-modified ?-hydroxyalkanoic acids are preferentially removed under stronger alkaline conditions. Saturated ?-hydroxyalkanoic acids are found to be abundant in all suberin extracts. These results are consistent with two distinct suberin fractions with different locations in cork cell walls and/or esterification degrees. It is proposed that these fractions correlate with the two main suberin peaks in the solid state 13C NMR spectra of cork and suberin extracts. Quantitative GC-MS analysis showed that suberin monomers comprise ?30% (w/w) of the suberin extracts, the remaining comprising nonvolatile structures with high Mn values, as measured by vapor pressure osmometry. The presence of a large fraction of high molecular weight aliphatic structures in suberin extracts is supported by the corresponding NMR spectra. Keywords: Suberin; cork; Quercus suber L.; GC-MS; NMR; alkaline methanolysis
doi: 10.1021/jf9909398doi: 10.1021/jf9909398The following values have no corresponding Zotero field: publisher: American Chemical Society